Double‐Object Constructions in Syrian Arabic. (9th July 2018) - Hallman, Peter
Abstract: This article documents double‐object constructions in contemporary Syrian Arabic and presents an analysis of the case‐frame alternations found there. Some double‐object verbs assign accusative case to their indirect object, as in English, while others assign it dative, as in German. Yet, for both verb types, the double‐object frame productively alternates with a frame in which the indirect object occurs in a prepositional phrase. Consequently, dative has, at the same time, properties of a lexical case (it is contingent on its lexical environment) but also properties of a structural case (it is suppressed in the prepositional frame). Further, restrictions on cliticization, animacy, and idiom patterns indicate that the prepositional frame of verbs displaying a double‐object frame is derived from the underlying double‐object frame. An analysis is presented in which D‐feature checking enforces the order indirect object > direct object in the double‐object frame regardless of the case of the indirect object, and the alternation between dative, accusative, and the prepositional frame is contingent on properties of the applicative head that θ ‐licenses the indirect object.